ANALYSIS OF CONSTRUCTIVIST LEARNING THEORY IN ARABIC LANGUAGE LEARNING AT FADHILLAH MIDDLE SCHOOL, PEKANBARU - Muhammad Ajiji Lubis; Muhammad Rifqi Ananda; Hakmi Wahyudi; Nandang Syarif Hidayat; Masbukin, Masbukin; Sri Wahyuni Hakim (Journal of Innovation Research and Knowledge, 2024)
Until now, the goal of education is to form individuals with spiritual strength, self-control, personality, intelligence, good morals, and skills that are useful for society. The learning process involves individuals actively in building knowledge through interaction with the environment, using approaches such as behaviorism, cognitive, and constructivism. Constructivism emphasizes that knowledge is the result of individual construction, which requires methods such as trial and error, dialogue, and active participation of students. In this context, this study focuses on the application of constructivism learning theory in Arabic language learning at Madrasah Tsanawiyah Fadhillah Pekanbaru. The research method used is qualitative with descriptive analysis, through interviews with the head of the madrasah and Arabic language teachers. The results of the study indicate that teachers have applied constructivism theory well, especially in vocabulary learning (mufradat) and kalam (speaking). However, there are several problems, such as the inability to apply this theory in each meeting due to limited time for assignments, as well as the lack of focus of some students during discussions.